Induction of p53 suppresses chronic myeloid leukemia. Issue 9 (2nd September 2017) - Peterson, Luke F.; Lo, Miao-Chia; Liu, Yihong; Giannola, Diane; Mitrikeska, Emilija; Donato, Nicholas J.; Johnson, Craig N.; Wang, Shaomeng; Mercer, Jessica; Talpaz, Moshe
Abstract: Chronic myeloid leukemia (CML) is characterized by the chromosomal translocation 9;22, known as the Philadelphia chromosome (Ph), which produces the BCR-ABL fusion tyrosine kinase. Although well-managed by BCR-ABL tyrosine kinase inhibitors (TKIs), treatment fails to eliminate Ph + primitive progenitors, and cessation of therapy frequently results in relapse. The p53 protein is an important regulator of cell cycle and apoptosis. The small molecules MI-219 target the interaction between p53 and its negative regulator HDM2, leading to its stabilization and activation. We show that treatment with MI-219 reduced the number of CML cells in both in vitro and in vivo settings but not that of normal primitive progenitors, and activated different gene signatures in CML potentially explaining the differential impact of this agent on each population. Our data suggest that a p53-activating agent may be an effective approach in the management and potential operational cure of CML.